2015
DOI: 10.1002/cctc.201500190
|View full text |Cite
|
Sign up to set email alerts
|

Suzuki–Miyaura Diversification of Amino Acids and Dipeptides in Aqueous Media

Abstract: The Suzuki-Miyaura derivatisation of free amino acids, peptides and proteins is an attractive area with much potential utility for medicinal chemistry and chemical biology. Here we report the modification of unprotected and Boc-protected aromatic amino acids and dipeptides in aqueous media, enabling heteroarylation and vinylation. We systematically investigate the impact of the peptide backbone and adjacent amino acid residues upon the reaction. Our studies reveal that whilst asparagine and histidine hinder th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 92 publications
1
34
0
Order By: Relevance
“…The functional group compatibility of Suzuki-Miyaura reactions with peptidic substrates has recently been reviewed elsewhere. 22, 27 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The functional group compatibility of Suzuki-Miyaura reactions with peptidic substrates has recently been reviewed elsewhere. 22, 27 …”
mentioning
confidence: 99%
“…Catalyst screening showed that the PdCl 2 (dppf) catalyst, which was shown to be compatible to peptide diversification in solution phase, 22 allowed to prepare the cross-coupled products with excellent conversions on support. Hence, the cross-couplings on solid-phase were realized with PdCl 2 (dppf) (10 mol%) as the precatalyst system in combination with K 2 CO 3 (5 eq) and (hetero)aromatic boronic acids (3 eq).…”
mentioning
confidence: 99%
“…Alteration of the ligand to sulfonated 2-dicyclohexylphosphino-2'-6'-dimethoxybiphenyl (SSPhos) was necessary to maintain the applicability of the Suzuki-Miyaura reaction on 7-Cl-tryptophans, as beautifully illustrated by derivatization of the natural product chloropacidamycin in mixed aqueous conditions (water/acetonitrile (AcN) 5:1) [96]. The synthesis of 7-vinyltryptophan 29 with potassium vinyltrifluoroborate and PdCl 2 (dppf), starting from 7-iodotryptophan 28 in mixed aqueous conditions ( Figure 6B), broadened the scope of halotryptophan derivatization, along with the derivatization of unprotected bromotryptophan and bromotryptophan-containing dipeptides [97]. Recently, Frese et al combined a biocatalytic and regioselective tryptophan halogenation and Suzuki-Miyaura cross-coupling in a multi-step one-pot reaction [98].…”
Section: Access To and Derivatization Of (Pseudo)halogenated Aromaticmentioning
confidence: 99%
“…As the Suzuki-Miyaura reaction is performed in basic conditions, the base labile 9-fluorenylmethyloxycarbonyl (Fmoc) protecting group is often not considered as part of a substrate. Nevertheless, Willemse reported Fmoc-iodophenylalanine as a substrate, and in their hands demonstrated that at 80 °C Fmoc-deprotection occurs when using PdCl2(dppf) in mixed aqueous conditions (iPrOH/H2O 1:1) with K2CO3 (not shown) [97]. However, by lowering the reaction temperature to 40°C, no deprotection occurred, but the reaction only reached a maximum conversion of 80% after 24 h. Similarly, Maity et al investigated the fluorescent properties of an amino acid containing a 4'-acetamido[1,1'-biphenyl] moiety [99].…”
Section: Access To and Derivatization Of (Pseudo)halogenated Aromaticmentioning
confidence: 99%
See 1 more Smart Citation